Trajectory control of a mobile manipulator in the presence of base disturbance. (June 2019) - Ram, RV; Pathak, PM; Junco, SJ
A mobile manipulator is typically an assembly of a mobile robot base and an on-board manipulator arm. As the manipulator arm is mounted over the mobile robot base, the controller has the additional task of taking care of the disturbances of the mobile robot due to the dynamic interactions between the mobile robot base and manipulator arm. In the present work, dynamic models for the manipulator arm and an omni-wheeled mobile robot base were developed separately and then both were combined. Two control strategies, namely only manipulator arm control (OMAC) and simultaneous manipulator and base control (SMBC) were developed for the effective control of tip trajectory. In both strategies, an amnesia recovery coupled with classical proportional integral and derivative (PID) control was used. The bond graph methodology was used for the development of the dynamic model and control for the mobile manipulator. Simulation results are presented to illustrate the efficacy of the two control strategies.